Archaeologica et historica - Castrén, Matthias Alexander 1813-1852 (Finno-Ugrian Society, 2017)
Matthias Alexander Castrén (1813-1852) was by far the most significant Finnish linguist of the 19th century. In addition to being a linguist he was also a multidisciplinary scholar, equally versatile in the fields of ethnography, folklore, mythology, archaeology, history, and human geography. He left behind a huge corpus of field data, collected by himself during prolonged expeditions to Karelia, Lapland, Arctic Russia, and Siberia between 1838 and 1849. In the short periods of time Castrén spent in an academic environment, he had little opportunity to synthesize his collections, a situation aggravated by his rapidly progressing and ultimately fatal illness. Therefore, a major part of his scholarly heritage remained unpublished when he died. Castrén's aim was to find the original homeland of the Finns. He approached this question with the aid of linguistics, folklore, archaeology, and history. Castrén was appointed Docent of Finnish and Ancient Nordic Languages and Tribes at the Imperial Alexander University in Helsinki in 1841, and ten years later he became the first Professor of the Finnish Language. As an academic professor, he emphasized the scholarly community's duties to society outside of academia. This volume contains Castrén's archaeological and historical writings as well as texts connected to his activities as a university professor.
Keywords: Castrén, Matthias Alexander -- 1813-1852; Geschichte; Finnougrische Sprachen; Ethnologie; Archäologie; Linguistik; Finnland